The “grave risk exception”, efficiency and the Hague Convention on Child Abduction: a Law and Economics Approach - Natália Camba Martins; Gustavo Ferreira Ribeiro (Revista Opinião Jurídica, 2019)
Contracting States adopted the Hague Convention on Child Abduction in 1980 after an extensive negotiation effort. The fi nal text added exceptions to the primary objective of prompt return of children wrongfully abducted to a country different from the one he/she habitually resided. Among them, the grave risk exception deals with situations in which the child, upon its return, may face physical or psychological harm or otherwise be placed in an intolerable situation. We posit in this paper that the elaboration and the evolution of this exception have been effi cient-prone in terms of legal design. To support our claim, the paper draws on the methodology of law and economics, more specifi cally on the standard and rules debate. The research demonstrates that the representatives of States faced heightened costs of specifi cations and low frequency of cases, which suggested the adoption of a standard. Moreover, nowadays, enduring specifi cation costs (which prompt for standards) and the elaboration of a Guide of Good Practices related to the concerned exception appear to be the best alternative available to advance its implementation. Therefore, on both its origin and evolvement, the exception follows an effi cient framework in terms of legal design.